IMPLEMENTASI KEBIJAKAN PEMERINTAH KABUPATEN PONOGORO DALAM PENETAPAN STATUS KEJADIAN LUAR BIASA (KLB) WABAH DEMAM BERDARAH DENGUE (DBD) DI KABUPATEN PONOROGO - Anisak, Khoirul; Dewi, Dian Suluh Kusuma (UIR PRESS, 2019)
Dengue Hemorrhagic Fever (DHF) is one of the public health problems that occurs in Indonesia with the number of sufferers that continues to increase and the wider spread in line with increasing mobility and population density. Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue virus and spread by mosquitoes, especially the Aedes Aegypti mosquito species. In 2016 Dengue Hemorrhagic Fever (DHF) is still a problem in Ponorogo Regency. Besides having the potential to cause Extraordinary Events (KLB), for the past nine years, Ponorogo Regency has become an Endemic District. According to data from the recapitulation of dengue cases in the Department of Health The high number of dengue cases in Ponorogo in 2019 were 17 sub-districts affected by dengue, with a total of 973 patients and 9 deaths. The high number of dengue fever is caused by an unstable climate and quite a lot of rainfall in the rainy season which is a potential breeding facility for Aedes aegypti mosquitoes. Besides that, it is also supported by the non-maximum activities in eradicating mosquito nests (PSN) in the community, causing an Extraordinary Event (KLB). Issues regarding how the implementation of the Ponorogo Regency government policy in determining the status of Extraordinary Events (KLB) outbreaks of Dengue Hemorrhagic Fever (DHF). Research on the implementation of the Ponorogo district government policy in determining the status of Extraordinary Events (KLB) outbreaks of Dengue Hemorrhagic Fever (DHF) in Ponorogo Regency using descriptive qualitative research methods with purposive sampling technique. The implementation of the policy in determining the DBD KLB so far can be said to be going well, this can be seen from the implementation in the field and the officers who are always on alert with the case.